Analysis of Solar Power Plants and Its Application for Power Supply of Screw Pumps in Wastewater PT. POMI - Cahyo, Septiyan Eko (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2022)
The  Cultivation  of  Domestic  wastewater  at  PT.  POMI  uses  the  addition  of  a  screw  pump  which  is carried out to overcome the problem in the storage tank, where the previous submersible pump type cannot work due  to  changes in  the content  of  wastewater  containing  fiber, causing the  pump impeller  get  stuck in  the  waste fiber pump and the pump cannot work. The screw pump is considered to be very powerful and efficient to drain waste containing water, sand, mud and fiber and this pump uses an alternative energy source so that it is more efficient and does  not  burden the electricity  generated  by  PLN.  Utilization of  solar energy  as  a  pump  resource can reduce the use of fossil fuels used by PLTU as fuel. Measuring the effectiveness of the screw pump is done by sampling  to  compare  the  output  of  waste  water  entering  the  reservoir  with  the  screw  pump  output  to  the  next process. The weather factor is one of the weaknesses of using solar panels. The energy needed to drive a pump of 8.1 kWh requires 21 solar panels with a capacity of 100 Wp  which can produce energy of 400 Wh per panel with with parallel 4 configuration with a capacity of 100 Wp per panel.